Echocardiographic Parameters of Severity in Isolated Neonatal Patent Ductus Arteriosus - Baher M. Hanna; Sandra S. Nashed; Mourad A. Tadros; Zahraa E. Osman (Cairo University, Faculty of Medicine, Department of Pediatrics, 2021)
Background: A hemodynamically-significant patent ductus arteriosus (hsPDA) compromises the early neonatal transition. There is no general agreement on echocardiographic indicators of hsPDA that can predict clinical decompensation. Aim of the Work: We aimed to assess echocardiographic parameters that are associated with the isolated PDA effects on hemodynamics, which could help in subsequent management decision making. Materials and Methods: We conducted a prospective observational analytical study on 50 neonates with isolated PDA and 20 controls. They underwent clinical and echocardiographic assessment at 48 hours of age, after another 48-72 hours and prior to discharge. Results: No correlation was found between PDA diameter and weight (p=0.72), length (p=0.11), Body surface area (BSA) (p=0.33), gestational age (p=0.13). A strong association of PDA-related hemodynamic instability was found with pulmonary hypertension (p=<0.01 & 0.05 for initial and latter studies). Left atrium diameter (LA) Z-score was higher among cases, correlated with PDA size in the 3 echocardiographic studies (p=0.001, 0.001 and 0.007 respectively), and correlated with hemodynamic instability in the initial study (p=0.03). Diameter of descending aorta at level of diaphragm and pulmonary flow/systemic flow ratio (Qp:Qs) correlated with PDA diameter in the latter 2 studies (p=0.001). Main pulmonary artery and left pulmonary artery (LPA) Z-scores were correlated with PDA size at the initial and follow-up studies as expected (p=0.001, 0.047 & 0.047; and p=0.004, 0.018 & 0.032, respectively). LPA Z-score correlated with hemodynamic instability at the follow-up study (p=0.005), which was not sustained at the subsequent study. Conclusion: Pulmonary hypertension, larger LA Z-score and LPA Z-scores are important early (at 48 hours) associations of a hsPDA and hemodynamic instability.